2016
DOI: 10.1038/srep21051
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a Carbohydrate-processing Transglycosidase into Glycosyltransferase for Natural Product Glycodiversification

Abstract: Glycodiversification broadens the scope of natural product-derived drug discovery. The acceptor substrate promiscuity of glucosyltransferase-D (GTF-D), a carbohydrate-processing enzyme from Streptococcus mutans, was expanded by protein engineering. Mutants in a site-saturation mutagenesis library were screened on the fluorescent substrate 4-methylumbelliferone to identify derivatives with improved transglycosylation efficiency. In comparison to the wild-type GTF-D enzyme, mutant M4 exhibited increased transgly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 62 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…Glycosylation reactions catalyzed by glucansucrases suffer from low thermodynamic favorability as pointed out by Liang et al ( 2016 ). The production of high catechol-G1 concentrations therefore requires an excess of donor substrate sucrose to drive the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycosylation reactions catalyzed by glucansucrases suffer from low thermodynamic favorability as pointed out by Liang et al ( 2016 ). The production of high catechol-G1 concentrations therefore requires an excess of donor substrate sucrose to drive the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The model acceptor substrate catechol was almost completely glycosylated into monoglycosylated product by the L981A mutant (93 % compared to 60 % for the wild-type enzyme), substantially higher than previously reported for catechol glycosylation by GtfD from S. mutans (65 %) (Meulenbeld and Hartmans 2000 ). In comparison, the I228A Np AS mutant only displayed a luteolin monoglycosylation yield of 53 % (Malbert et al 2014 ), whereas the GtfD mutant showed a catechin monoglycosylation yield of 90 % (Liang et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Site-saturation mutagenesis targeting the subsite +1 of GTF-D, Tyr418 and Asn469 (equivalent to Tyr430 and Asn481 of GTF180ΔN) was carried out and the mutant library was screened by quenching the fluorescence of coumarin 4-methylumbelliferone (4-MU) through glucosylation. The method enabled to isolate a mutant showing an improved ability for the glucosylation of coumarin 4-methylumbelliferone as well as genistein, daidzein silybin and catechin compared to the parental enzyme [ 210 ].…”
Section: Enzyme Engineering For Man-made α-Glucans Oligosaccharides and Glucoconjugatesmentioning
confidence: 99%
“…Transglycosylation reactions of AS are usually conjugations of single and/or multiple (gluco-oligosaccharides) sugar(s) with a great advantage compared with Leloir GTs. For production of bioactive phenolic glycosides [2,3], AS has been used in the synthesis of a variety of attractive biomaterials including amylose-like polymers, starch, dendritic nanoparticles, and microparticle encapsulation [4][5][6]. Although AS has potential application in glycodiversification, it is rarely reported for transglycosyation of phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%